Modulation of myocardial contraction by peroxynitrite - Kohr, Mark; Roof, Steve; Zweier, Jay; Ziolo, Mark T. (Frontiers in Physiology, 2012)
Peroxynitrite is a potent oxidant that is quickly emerging as a crucial modulator of myocardial function. This review will focus on the regulation of myocardial contraction by peroxynitrite during health and disease, with a specific emphasis on cardiomyocyte Ca2+ handling, proposed signaling pathways, and protein end-targets.